2011
DOI: 10.1016/j.cimid.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase protein changes in calves during an outbreak of respiratory disease caused by bovine respiratory syncytial virus

Abstract: Bovine acute phase proteins (APPs), lipopolysaccharide binding protein (LBP), serum amyloid A (SAA), haptoglobin (Hp) and alpha(1)-acid glycoprotein (AGP) were evaluated as inflammatory markers during an outbreak of bovine respiratory disease (BRD) caused by bovine respiratory syncytial virus (BRSV). Calves (n = 10) presented mild to moderate signs of respiratory disease. Secondary bacterial infections, Pasteurella multocida and Mycoplasma dispar as major species, were detected in tracheobronchial lavage sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 31 publications
7
49
1
Order By: Relevance
“…Moreover, the infusion of high concentrations of pro-inflammatory cytokines in rabbits was associated with multiple organ dysfunction syndrome (Kusawa et al 1988). Several studies have suggested that the circulating levels of proinflammatory cytokines could be useful in assessing the severity and in predicting the clinical outcomes of some diseases (Rauchhaus et al 2000;Orro et al 2011;El-Ashker et al 2013;El-Ashker et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the infusion of high concentrations of pro-inflammatory cytokines in rabbits was associated with multiple organ dysfunction syndrome (Kusawa et al 1988). Several studies have suggested that the circulating levels of proinflammatory cytokines could be useful in assessing the severity and in predicting the clinical outcomes of some diseases (Rauchhaus et al 2000;Orro et al 2011;El-Ashker et al 2013;El-Ashker et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, other findings demonstrated either lower or unaltered Hp values of infected cows. The significant (P≤0.05) elevation of SAA of pneumonic camelcalves (Table 4) could be attributed to the physiological role of SAA in host defense during inflammation (Orro et al, 2011). Recently, similar marked elevation (P≤0.05) of SAA was reported in pneumonic calves (Nikunen et al, 2007;Orro et al, 2011) and pneumonic buffalo calves (El-Deeb, 2011;El-Bahr & El-Deeb, 2013).…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 50%
“…The significant (P≤0.05) elevation of SAA of pneumonic camelcalves (Table 4) could be attributed to the physiological role of SAA in host defense during inflammation (Orro et al, 2011). Recently, similar marked elevation (P≤0.05) of SAA was reported in pneumonic calves (Nikunen et al, 2007;Orro et al, 2011) and pneumonic buffalo calves (El-Deeb, 2011;El-Bahr & El-Deeb, 2013). Fibrinogen (Fb) is a reliable indicator of inflammation and/or bacterial infection in cattle and sheep (Nikunen et al, 2007;Gonzalez et al, 2008;Orro et al, 2011).…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 58%
“…Conversely, there have been several investigations into the acute phase response during both naturally-occurring and experimentally-induced bovine diseases. In studies of bovine respiratory disease, peak levels of serum SAA and HPT were reported during week 3 of an outbreak of respiratory disease in calves caused by respiratory syncytial virus (Orro et al, 2011), while experimental infection with respiratory syncytial virus caused maximal increases in serum levels of HPT and SAA in cattle as early as 7-8 days following inoculation (Heegaard et al 2000). Of the bovine diseases studied, however, APP expression has been investigated most extensively during mastitis in lactating dairy animals (Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2006Eckersall et al, , 2001Grönlund et al, 2003;Hirvonen et al, 1999).…”
Section: Modulation Of Acute Phase Proteins During Ruminant Diseasementioning
confidence: 99%
“…Veterinary Biomarker Discovery: Proteomic Analysis of Acute Phase Proteins 191 2.1 Modulation of acute phase proteins during disease in swine Alteration in APP expression has been associated with a number of food animal diseases (Table 1), including mastitis, metritis, and amyloidosis in lactating dairy cattle (Chan et al, 2010;Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2001Eckersall et al, , 2006Takahashi et al, 2006;Grönlund et al, 2003Grönlund et al, , 2005; sepsis, trauma, and respiratory diseases in swine (Amory et al, 2007;Sorensen et al, 2006;Hultén et al, 2003;Heegaard et al, 1998;Eckersall et al, 1996); infectious bronchitis virus in chickens (Nazifi et al, 2011); respiratory diseases in beef cattle (Orro et al, 2011;Heegaard et al, 2000;Godson et al, 1996;Horadagoda et al, 1995); as well as pulmonary damage and caseous lymphadenitis in sheep (Eckersall et al, 2007;Pfeffer and Rogers, 1989 In swine, increased levels of serum HPT have been associated with pathological indications of Mycoplasma hyopneumoniae, a leading cause of porcine enzootic pneumonia (Amory et al, 2007). Similarly, serum concentrations of HPT and SAA were elevated in pigs with experimentally induced Actinobacillus pleuropneumoniae pneumonia Heegaard et al, 1998).…”
Section: Wwwintechopencommentioning
confidence: 99%